Differences in Seizure Expression Between Magnetic Seizure Therapy and Electroconvulsive Shock. Issue 2 (June 2018) - Cycowicz, Yael M.; Rowny, Stefan B.; Luber, Bruce; Lisanby, Sarah H.
Abstract : Objective: Evidence suggests that magnetic seizure therapy (MST) results in fewer side effects than electroconvulsive treatment, both in humans treated with electroconvulsive therapy (ECT) as well as in the animal preclinical model that uses electroconvulsive shock (ECS). Evidence suggests that MST results in fewer cognitive side effects than ECT. Although MST offers enhanced control over seizure induction and spread, little is known about how MST and ECT seizures differ. Seizure characteristics are associated with treatment effect. This study presents quantitative analyses of electroencephalogram (EEG) power after electrical and magnetic seizure induction and anesthesia-alone sham in an animal model. The aim was to test whether differential neurophysiological characteristics of the seizures could be identified that support earlier observations that the powers of theta, alpha, and beta but not delta frequency bands were lower after MST when compared with those after ECS. Methods: In a randomized, sham-controlled trial, 24 macaca mulatte received 6 weeks of daily sessions while scalp EEG was recorded. Electroencephalogram power was quantified within delta, theta, alpha, and beta frequency bands. Results: Magnetic seizure therapy induced lower ictal expression in the theta, alpha and beta frequencies than ECS, but MST and ECS were indistinguishable in the delta band. Magnetic seizure therapy showed less postictal suppression than ECS. Increasing electrical dosage increased ictal power, whereas increasing MST dosage had no effect on EEG expression. Conclusions: Magnetic seizure therapy seizures have less robust electrophysiological expression than ECS, and these differences are largest in the alpha and beta bands. The relevance of these differences in higher frequency bands to clinical outcomes deserves further exploration. Significance: Contrasting EEG in ECS and MST may lead to insights on the physiological underpinnings of seizure-induced amnesia and to finding ways to reduce cognitive side effects.